Pengaruh pH dan Ukuran Partikel Terhadap Penyerapan Malachite Green Menggunakan Biosorben Dari Kulit Langsat (Lancium domesticum) - Sutan M Razali; Desy Kurniawati; Edi Nasra; Miftahul Khair (Departemen Kimia FMIPA UNP, 2022)
The malachite green dye is one of the harmful dyes produced from various textile industry wastes and needs to reduce by the presence of the waste. The biosorption method is one of the alternative methods used to remove the concentration of malachite green. Biosorption using langsat peel biosorbent proved to be able to absorb malachite green dye. This study using the coloum method by varying the pH of the MG solution and particle size of the biosorbent. In this research, spectronics were used to measure the concentration of the solution and analyze the functional groups on langsat peel before activation, after activation, and after contact using FTIR. Based on the results of the study, it was found that the optimum conditions for each variation were at solution pH 5 with an adsorption rate of 4.962 mg/g and particle size of biosorbent 106 m with an adsorption rate of 15.376 mg/g.